Teaching Portuguese for foreigners in Rio de Janeiro/Brazil: interview with Norimar P. Judice and Rosa Marina B. Meyer - Ribeiro, Alexandre do Amaral (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2018)
An interview with two of renowned pioneers of teaching Portuguese for foreigners in Rio de Janeiro/Brazil: professors Norimar P. Judice and Rosa Marina B. Meyer. They were asked four questions about their careers, their opinion on the area’s current situation and their expectations for the future of this ever-growing area. ———————————————————————————— ENSINO DE PORTUGUÊS PARA ESTRANGEIROS NO RIO DE JANEIRO/BRASIL: ENTREVISTA COM NORIMAR P. JUDICE AND ROSA MARINA B. MEYER Uma entrevista com dois dos renomados pioneiros do ensino de português para estrangeiros: professores Norimar P. Judice e Marina B. Meyer. Foram feitas quatro perguntas sobre suas carreiras, suas opiniões sobre a situação atual da área e suas expectativas para esta área sempre em crescimento.